Factors associated with lip and oral cavity cancer - Isabella Lima Arrais Ribeiro; Júlia Julliêta de Medeiros; Larycia Vicente Rodrigues; Ana Maria Gondim Valença; Eufrásio de Andrade Lima Neto (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2015)
PURPOSE: This study aimed to identify factors associated with the occurrence of primary cancer of the lip and oral cavity regions compared to other types of head and neck cancers according to demographic, socioeconomic data and lifestyle, in Brazil, from 2000 to 2011. METHODS: A study was conducted using Hospital Cancer Records (Instituto Nacional do Câncer), from 2000 to 2011, totaling 23,153 cases. Data were analyzed by binary logistic regression (response category: primary cancers located in the lip and oral cavity; comparison category; other types of primary cancer in the head and neck, which does not affect the lip and oral cavity) at a significance level α = 5%. RESULTS: The study showed factors associated with higher incidence of cancer in the lip and oral cavity: being of advanced age (OR = 1.16), not having a family history of cancer (OR = 2.38), alcohol consumption (OR = 1.17); former tobacco use (OR = 1.51) or current tobacco use (OR = 1.65); having a previous diagnosis of cancer without treatment (OR =1.66). Being female (OR = 0.92), having completed basic (OR = 0.71) and higher (OR = 0.46) education and having previous diagnosis of cancer with treatment (OR = 0.74) constituted factors associated with lower prevalence of cancer of the lip and oral cavity. CONCLUSION: Age, absence of family history of cancer, smoking habits and alcohol consumption, and previous diagnosis of cancer without treatment were associated with a higher incidence of cancer of the lip and oral cavity.